PENGARUH LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN KELUARGA DI MASA PANDEMI COVID-19 DENGAN SELF EFFICACY SEBAGAI VARIABEL INTERVENING - Ina Khodijah; Raden Irna Afriani; Yuliah Yuliah; Yollanda Octavitri (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The effect of the PSBB or PPKM implemented by the government has changed the economic life of the Indonesian people in general, so that housewives must be able to manage their family finances well. With her knowledge and confidence in managing every family's expenses by adjusting her husband's income. This study aims to examine the effect of Financial Literacy and Financial Attitude on Financial Management Behavior of Women Farmers Group with Self Efficacy as Intervening Variable. This research is a quantitative research with data collection techniques using a questionnaire. The sample is 30 respondents. The sampling technique used is saturated sampling. Primary data processing using path analysis techniques using SMART PLS 3 software. he results of the research hypothesis 1 have a P value of 0.001 so that it rejects Ho and accepts Ha. Hypothesis 2, obtained a P value of 0.027 so that it rejects Ho and accepts Ha. Hypothesis 3, the result of P value is 0.781 so that it accepts Ho and rejects Ha. Hypothesis 4, the result of P value is 0.450 so that it accepts Ho and rejects Ha. And hypothesis 5, the result of P value is 0.773 so that it accepts Ho and rejects Ha. The conclusion is that financial literacy has a significant effect on financial management behavior, while financial attitudes have a significant effect on financial management behavior. And Self Efficacy has no influence on financial management behavior. In addition, the results of the study show that Self Efficacy is not able to mediate financial literacy on financial management behavior and is also unable to mediate between financial attitudes and financial management behavior